2014
DOI: 10.12691/ajps-2-1-4
|View full text |Cite
|
Sign up to set email alerts
|

Self Medication Practice among Iraqi Patients in Baghdad City

Abstract: The practice of self medication is continuously increasing worldwide due to its important roles in curing minor conditions or symptoms. This study was conducted to evaluate the factors associated with self medication practice of Iraqi respondents residing in Baghdad City. This study was designed as cross sectional study in which data was collected via direct interviews with respondents using a previously prepared questionnaire. This study investigated 348 respondents from different age groups. The majority of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 20 publications
3
18
1
2
Order By: Relevance
“…Similarly, the patient’s assessment of their ailment as minor was identified as one of the major factors in self-medication in many studies conducted outside Ethiopia 27–35. Prior experience of treating the same condition by self-medication has also been mentioned as the main reason for practicing self-medication 34,35. Studies conducted in other developing countries also mention lack of time to visit the physician and economic problems as the main reason to use self-medication 23,33…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the patient’s assessment of their ailment as minor was identified as one of the major factors in self-medication in many studies conducted outside Ethiopia 27–35. Prior experience of treating the same condition by self-medication has also been mentioned as the main reason for practicing self-medication 34,35. Studies conducted in other developing countries also mention lack of time to visit the physician and economic problems as the main reason to use self-medication 23,33…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies conducted to assess the practice of self-medication outside Ethiopia also reported analgesics as the most widely consumed OTC drugs in self-care 22,23,35,4043. Antimicrobials were also reported in many studies as commonly used drugs in self-medication 23,34,37,44–46. One review article indicated that the overall estimate of antimicrobial self-medication in low- and middle-income countries was 38.8% 47.…”
Section: Discussionmentioning
confidence: 99%
“…Fever and cold were indicated as the most frequent health complaint that led to self-medication in different studies [ 42 - 43 ]. There were also studies that reported respiratory diseases [ 44 ] and gastrointestinal (GI) tract diseases [ 45 ] as common illnesses for which self-medication was used. This may be because these illnesses are very common and occur frequently in individuals with experience in treating them.…”
Section: Reviewmentioning
confidence: 99%
“…whether patients can afford to see both a physician and purchase their medicines) and economic benefits. In some situations, pharmacists are the only healthcare professionals available to patients 47,[128][129][130][131][132][133][134][135][136][137][138][139][140][141] . Self-purchasing of antimicrobials is particularly problematic in LMICs compared with high income countries 49,52,120,121,123,142,143 .…”
Section: Introductionmentioning
confidence: 99%